Critical realism, mimetic theory and social work. (March 2022) - Houston, Stan; Swords, Calvin
Summary: Scapegoating is a ubiquitous, yet pernicious, phenomenon in today's world. It manifests in innumerable ways. Social work, in line with its emancipatory value-base, seeks to engage with various scapegoated groups to challenge the experience. In this article, the authors draw on critical realism and mimetic theory to elucidate the causative mechanisms fuelling scapegoating. This is done in order to heighten social workers' insight into the process and empower targeted groups. Findings: Mimetic theory highlights that scapegoating is a product of desire, rivalry and deflection. These are deep-seated mechanisms that are compatible with critical realist ontology and its search for causative properties in the social world. It is argued that critical realism augments mimetic theory by setting it within a much wider and deeper context of understanding. As such, it emphasizes intersecting causes and contingencies such as the role of temporal and spatial factors shaping the scapegoating experience. Applications: Social workers can transform these theoretical insights into sensitizing constructs when they facilitate self-directed groupwork with scapegoated groups. Being theoretically informed, they can pose critical questions to group members to assist them to make the link between personal problems and political issues. The aim is to empower these groups so that they can embrace the sociological imagination and act for change.